2022
DOI: 10.3390/ijns8010009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Methods for Quantification of Glycosaminoglycan Biomarkers in Newborn Dried Blood Spots from Patients with Severe and Attenuated Mucopolysaccharidosis Type II

Abstract: All newborn screening (NBS) for mucopolysaccharidosis-I and -II (MPS-I and MPS-II) is carried out via the measurement of α-iduronidase (IDUA) and iduronate-2-sulfatase (IDS) enzymatic activity, respectively, in dried blood spots (DBS). The majority of low enzyme results are due to pseudodeficiencies, and data from recent MPS-II population screenings and studies from the Mayo Clinic show that the false positive rate can be dramatically reduced by the inclusion of a second-tier analysis of glycosaminoglycans (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Thus, genetic testing is often conducted in many NBS programs to verify the patients with low enzyme activity. In addition, recent data have shown that a second‐tier analysis of biomarkers appears to be a powerful tool to reduce high false positive rates associated with pseudo deficiencies in NBS of Krabbe disease, MPS I, and MPS II 35–37 …”
Section: Enzymatic Activity Testing‐based Nbs For Lsdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, genetic testing is often conducted in many NBS programs to verify the patients with low enzyme activity. In addition, recent data have shown that a second‐tier analysis of biomarkers appears to be a powerful tool to reduce high false positive rates associated with pseudo deficiencies in NBS of Krabbe disease, MPS I, and MPS II 35–37 …”
Section: Enzymatic Activity Testing‐based Nbs For Lsdsmentioning
confidence: 99%
“…In addition, recent data have shown that a second‐tier analysis of biomarkers appears to be a powerful tool to reduce high false positive rates associated with pseudo deficiencies in NBS of Krabbe disease, MPS I, and MPS II. 35 , 36 , 37 …”
Section: Enzymatic Activity Testing‐based Nbs For Lsdsmentioning
confidence: 99%
“…Finally, it is important that screening methods minimize the potential false positives from heterozygous individuals and from pseudodeficiency alleles as well as the uncertain findings of variants of unknown significance by adopting optimal second tier evaluations of disease biomarkers using dried blood spot (DBS) samples (Clarke et al, 2020;Peck et al, 2020). Advocacy groups have a role in this effort, and can assist as the Society has, in procuring consented access to patient DBS, which facilitated the further development and validation of DBS glycosaminoglycans as biomarkers of MPS I and MPS II (Herbst et al, 2020(Herbst et al, , 2022.…”
Section: Standards Of Diagnosis and Carementioning
confidence: 99%
“…Specific GAG nonreducing end species (GAG-NREs) have been validated as biomarkers for diagnosis, severity classification, and response to therapy in several MPS disorders. 8,9,11,12,[14][15][16][17] In single sulfatase MPS disorders, a single enzyme is deficient leading to accumulation of that enzyme's specific GAG-NRE substrate. In MSD, multiple enzymes are deficient, so we hypothesize that several GAG-NREs will accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple methods have been developed to evaluate GAG degradation products. Here, we utilize three previously reported techniques: (1) the "internal disaccharide" method, 18,19 where GAG polymers are degraded in vitro with bacterial enzymes into resultant disaccharides, which are quantified via LC-MS/MS; (2) the "Sensi-Pro ® " method, 8,11,20 which quantifies the GAG non-reducing end (GAG-NRE) fragment via LC-MS/MS after its in vitro liberation from the GAG polymer via bacterial enzymes; and (3) the "endogenous NRE" method, [15][16][17] which quantifies small endogenously produced GAG-NRE fragments from patient samples without in vitro degradation. These techniques show variable sensitivity and specificity when applied to single sulfatase disorders.…”
Section: Introductionmentioning
confidence: 99%